Incorporating Sustainability in Facility Layout Planning Algorithms and Assessing Hybridization Techniques on an Egyptian Case Study - Atia, Islam (AUC Knowledge Fountain, 2025)
Due to the growing consequences faced as a result of global warming and climate change; humanity has come together to take an inclusive stance to combat this serious phenomena and work towards a more sustainable future. Large amounts of carbon dioxide emissions are a major contributor to global warming, and a vast proportion of this emission come from industrial and commercial facilities. Hence, if industrial facilities are built with a larger focus on carbon footprint, it will yield a significant reduction in global emissions throughout the lifetime of the facility and will constitute a huge milestone in the journey to Net Zero. This research focuses on advancing facility layout planning (FLP) methodologies through the integration of sustainability metrics and the combination of different layout improvement techniques. Using an industrial adhesives facility in Cairo as a case study, the study evaluates the effectiveness of ALDEP and CRAFT algorithms and their combination in achieving improved layouts. Key metrics include reductions in material handling (MH) costs, carbon dioxide emissions, and adjacency-based scoring (ABS) improvements. The study incorporates a quantitative carbon emission penalty factor to align cost efficiency with environmental sustainability, resulting in 27.3% annual cost saving in material handling costs, and 41% annual cost reduction in material handling costs factoring in the sustainability penalty. As shown by the mentioned cost reductions; replacing traditional diesel-powered material handling equipment (MHE) with electric alternatives, the improved facility layout achieved significant reductions in operational costs and environmental impact. The analysis highlights that ALDEP trial 5 provided the most efficient layout, with increased production rates, improved ABS, and significant cost and carbon emission reductions. Combination of ALDEP and CRAFT improved the performance of lower-quality layouts and the initial facility, but yielded no improvement for the best-performing ALDEP trial due to the size limitations and small scale of the facility. This study emphasizes the importance of incorporating sustainability metrics into FLP methodologies and provides a modified framework for designing cost-effective and environmentally sustainable industrial facilities.